Interactions Under Crowding Milieu: Chemical-Induced Denaturation of Myoglobin is Determined by the Extent of Heme Dissociation on Interaction with Crowders - Khalida Nasreen; Zahoor Ahmad Parray; Shahzaib Ahamad; Faizan Ahmad; Anwar Ahmed; Salman Freeh Alamery; Tajamul Hussain; Md. Imtaiyaz Hassan; Asimul Islam (Biomolecules, 2020)
Generally, in vivo function and structural changes are studied by probing proteins in a dilute solution under in vitro conditions, which is believed to be mimicking proteins in intracellular milieu. Earlier, thermal-induced denaturation of myoglobin, in the milieu of crowder molecule showed destabilization of the metal protein. Destabilization of protein by thermal-induced denaturation involves a large extrapolation, so, the reliability is questionable. This led us to measure the effects of macromolecular crowding on its stability by chemical-induced denaturation of the protein using probes like circular dichroism and absorption spectroscopy in the presence of dextran 70 and ficoll 70 at various pHs (acidic: 6.0, almost neutral: 7.0 and basic: 8.0). Observations showed that the degree of destabilization of myoglobin was greater due to ficoll 70 as compared to that of dextran 70 so it can be understood that the nature of the crowder or the shape of the crowder has an important role towards the stability of proteins. Additionally, the degree of destabilization was observed as pH dependent, however the pH dependence is different for different crowders. Furthermore, isothermal titration calorimetry and molecular docking studies confirmed that both the crowders (ficoll and dextran) bind to heme moiety of myoglobin and a single binding site was observed for each.